Field evaluation of cacao progenies derived from Guiana clones for yield and black pod disease resistance. Issue 1 (9th March 2020) - Ofori, Atta; Padi, Francis K.; Amoako‐Attah, Ishmael
Abstract: Phytophthora spp. is a major disease of cacao ( Theobroma cacao L.), and there is a need to develop cultivars that are resistant to this disease. Among the various genetic groups of cacao, the Guiana (GU) has received little attention in developing varieties even though they are known to be tolerant to black pod disease. The objective of this study was to estimate combining abilities and heritability of selected GU clones for bean yield and black pod resistance. Twenty‐four F1 progenies were derived by crossing three seed garden parental clones with eight GU clones as males in a three‐by‐eight North Carolina II (NC II) complete factorial mating design. These were evaluated together with four standard varieties over a 4‐yr period in a randomized complete block design with four replications at two contrasting locations in Ghana. Progeny, year, and location effects were significant ( p < .01) for all traits, whereas progeny × location was significant for only number of beans per pod. The general combining ability (GCA) effects of females and males and specific combining ability (SCA) of female × male were significant ( p < .01) for all traits, indicating that both additive and dominant effects are important in the inheritance of the traits. Heritability ranged from 0.14–0.51 for broad sense and 0.10−0.37 for narrow sense. The best general combiners identified—GU 125/C, GU 144/C, and GU 290/H—were involved in crosses that combines high bean yield with high black pod resistance. They could be added to parental clones currently used in producing cacao varieties in areas with high black pod incidence.